Effect of fortification of drinking water with iron plus ascorbic acid or with ascorbic acid alone on hemoglobin values and anthropometric indicators in preschool children in day-care centers in Southeast Brazil - Almeida, Carlos Alberto Nogueira de; Dutra-de-Oliveira, Jóse Eduardo; Crott, Gerson Claudio; Cantolini, Alessandro; Garcia Ricco, Rubens; Del Ciampo, Luiz Antonio; Costa Baptista, Marina Elisa (My University, 2005)
Background. Iron-deficiency anemia currently is the most frequently occurring nutritional disorder worldwide. Previous Brazilian studies have demonstrated that drinking water fortified with iron and ascorbic acid is an adequate vehicle for improving the iron supply for children frequenting day-care centers. Objective. The objective of this study was to clarify the role of ascorbic acid as a vehicle for improving iron intake in children in day-care centers in Brazil. Methods. A six-month study was conducted on 150 children frequenting six day-care centers divided into two groups of three day-care centers by drawing lots: the iron-C group (3 day-care centers, n = 74), which used water fortified with 10 mg elemental iron and 100 mg ascorbic acid per liter, and the comparison group (3 day-care centers, n = 76), which used water containing only 100 mg ascorbic acid per liter. Anthropometric measurements and determinations of capillary hemoglobin were performed at the beginning of the study and after six months of intervention. The food offered at the day-care centers was also analyzed. Results. The fo od offered at the day-care center was found to be deficient in ascorbic acid, poor in heme iron, and adequate in non-heme iron. Supplementation with fortified drinking water resulted in a decrease in the prevalence of anemia and an increase in mean hemoglobin levels associated with height gain in both groups. Conclusions. Fortification of drinking water with iron has previously demonstrated effectiveness in increasing iron supplies. This simple strategy was confirmed in the present study. The present study also demonstrated that for populations receiving an abundant supply of non-heme iron, it is possible to control anemia in a simple, safe, and inexpensive manner by adding ascorbic acid to drinking water. © 2005, The United Nations University.
Keywords: Anemia; Ascorbic acid; Dietary supplements; Drinking water; Growth; Iron deficiency; antioxidant; ascorbic acid; fresh water; hemoglobin; child health; diet; drinking water; nutrition; anthropometry; Brazil; chemistry; clinical trial; controlled clinical trial; controlled study; day care; diet supplementation; drug effect; female; human; iron deficiency anemia; iron intake; male; preschool child; randomized controlled trial; treatment outcome; Anemia, Iron-Deficiency; Anthropometry; Antioxidants; Ascorbic Acid; Child Day Care Centers; Child, Preschool; Female; Food, Fortified; Fresh Water; Hemoglobins; Humans; Iron, Dietary; Male; Treatment Outcome